The Analysis of the Quality of Life of Patients with Degenerative Changes in the Cervical Spine - Anna Antczak-Komoterska; Agnieszka Wasielewska; Beata Haor; Dorota Kochman; Wiesław Fidecki; Mariusz Wysokiński (Pielęgniarstwo Neurologiczne i Neurochirurgiczne, 2021)
Introduction. Degenerative diseases of the spine are a problem that threatens the modern population around the world. The World Health Organization (WHO) has recognized the degenerative changes of the spine as an epidemic of our times. Aim. The aim of the study was to assess the quality of life of patients with degenerative changes in the cervical spine in the context of sociodemographic data including: gender, age, education, marital status, type of work, place of residence, health problems, coexisting diseases and place of services. Material and Methods. 103 people were included in the study. Women constituted 60.2% of the respondents, while men 39.8%. The age of the respondents was between 25 and 76 years old. The tool used in this study was the WHOQoL-BREF questionnaire. The statistical analysis was performed based on the chi square test. The obtained results were analysed with the × 2 test for independent samples, the error rate of 5% was assumed. Results. The analysis of data concerning the place of residence showed a division into the urban environment of 79.6% and the rural environment constituting 20.4%, there was no correlation between the place of residence of the respondents and their quality of life in the social field. The respondents represented a varied level of education, the most numerous group were patients with vocational education 32%, because the complaints are often related to the type of work performed, the most numerous group were the retired persons/pensioners — 40.8%. The analysis showed a significant relationship between the work performed and education. Conclusions. Degenerative changes of the cervical spine and related ailments are among the most common health problems in people over 50 living in an urban environment. Women are statistically more likely to experience pain in the cervical spine due to the weaker muscle corset. The subjective assessment of the quality of life is positive. It was best assessed by people with higher education and respondents from the urban environment. (JNNN 2021;10(4):175–179)